METHODS AND APPROACHES TO TEACHING WRITING SKILLS IN A FOREIGN LANGUAGE: https://doi.org/10.5281/zenodo.20823888 - Odamoyev , Toxir; Abduraxmanova , Zilola (Scientific practical conference, 2026)
This article analyzes the methodological foundations of developing writing skills in foreign language teaching. Writing is considered not only as a set of grammatical and lexical knowledge but as a complex process of logical and coherent expression of ideas. The study compares the effectiveness of process-oriented and product-oriented approaches. The results indicate that interactive tasks and step-by-step writing techniques are essential in enhancing students' creative writing abilities and overall communicative competence.